2019
DOI: 10.1103/physrevlett.122.217001
|View full text |Cite
|
Sign up to set email alerts
|

Emergent Critical Charge Fluctuations at the Kondo Breakdown of Heavy Fermions

Abstract: One of the challenges in strongly correlated electron systems, is to understand the anomalous electronic behavior that develops at an antiferromagnetic quantum critical point (QCP), a phenomenon that has been extensively studied in heavy fermion materials. Current theories have focused on the critical spin fluctuations and associated break-down of the Kondo effect. Here we argue that the abrupt change in Fermi surface volume that accompanies heavy fermion criticality leads to critical charge fluctuations. Usin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
37
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 49 publications
(40 citation statements)
references
References 53 publications
3
37
0
Order By: Relevance
“…Near a Kondo-breakdown QCP, when the low-energy Fermi liquid scale T * vanishes, dynamical response quantities should obey ω/T scaling of the form σ (ω, T ) ∝ T −α f (hω/k B T ) with a universal scaling function f (x). This was theoretically expected [43,44] and experimentally found not only in CeCu 5.9 Au 0.1 for the dynamic magnetic response [31], but also more recently in YbRh 2 Si 2 for the optical conductivity [37]. Note that T * is to be distinguished from the Kondo lattice temperature T * K characterizing the onset of Kondo spin-screening and heavy quasiparticle formation.…”
Section: Resultssupporting
confidence: 64%
“…Near a Kondo-breakdown QCP, when the low-energy Fermi liquid scale T * vanishes, dynamical response quantities should obey ω/T scaling of the form σ (ω, T ) ∝ T −α f (hω/k B T ) with a universal scaling function f (x). This was theoretically expected [43,44] and experimentally found not only in CeCu 5.9 Au 0.1 for the dynamic magnetic response [31], but also more recently in YbRh 2 Si 2 for the optical conductivity [37]. Note that T * is to be distinguished from the Kondo lattice temperature T * K characterizing the onset of Kondo spin-screening and heavy quasiparticle formation.…”
Section: Resultssupporting
confidence: 64%
“…Because the magnetic quantum phase transition is accompanied by the transition from a phase with asymptotically decoupled local-moment and conductionelectron degrees of freedom to one in which the entangling of the two turns the 4f local moments into composite quasiparticles, it is natural that both the single-particle and charge dynamics are critical. Indeed, calculations at the Kondo-destruction QCP in various large-N limits (Cai et al, 2020;Kirchner et al, 2005;Komijani and Coleman, 2019;Zhu et al, 2004) and, more recently, in the physical N = 2 case (Cai et al, 2020) have shown such a singular charge dynamics. Intriguingly, this type of charge dynamical scaling in models of the Kondo limit smoothly connects to the ω/T -scaling for the charge dynamics in the beyond-Landau-type quantum criticality in the mixed-valence regime (Pixley et al, 2012).…”
Section: Discussionmentioning
confidence: 97%
“…8. Associated with the Kondo breakdown and development of a large Fermi surface, soft charge fluctuations can emerge without a change in formal valence of Ce ions 52 . Within experimental uncertainty of ±1.5%, there is no detectable difference between CeRhIn 5 and CeIrIn 5 at 10 K in their spectroscopically determined Ce valence 53 , even though their Fermi volumes differ-a result that, together with the phase diagram of Fig.…”
Section: Discussionmentioning
confidence: 99%